Parenting on the margins: a qualitative study of the challenges encountered by fathers of children with autism in Limpopo Province, South Africa - Nkgaphela, M. Rosinah; Sumbane, G. Olivia; Hlahla, L. Sebolaisi; Mokhwelepa, L. Winter (Frontiers in Psychiatry, 2026)
BackgroundAutism spectrum disorder (ASD) has a profound impact on families, including fathers, who often face multiple challenges while raising their children. Fathers of children with ASD frequently experience stress, financial difficulties, stigma, and limited support, which can negatively affect their wellbeing and caregiving capacity.MethodsA qualitative, phenomenological research design was employed to gain a detailed understanding of the challenges faced by fathers. Non-probability purposive sampling was used to recruit 15 fathers of children with ASD. Data were collected through semi-structured interviews and analyzed using Tesch’s eight steps of data analysis.ResultsThe findings showed challenges directly related to ASD, social challenges associated with caring for children with ASD, and service provision challenges experienced by fathers.ConclusionFathers of children with ASD face a wide range of difficulties that extend beyond caregiving and include difficulties in the management of behavioral problems, inadequate service support, and societal stigma. An effective intervention program should incorporate the unique challenges and experiences of fathers of children with ASD to ensure that they receive appropriate assistance. These findings can be used to monitor and evaluate the support provided to fathers of children with ASD.